STRATEGI PENINGKATAN DAYA SAING PADA PRODUK OLAHAN SAMBEL PECEL (STUDI KASUS PADA KOMUNITAS UMKM JURAGAN SAMBEL PECEL DI KOTA MADIUN) - Devi Istyalita; Mubarokah Mubarokah; Prasmita Dian Wijayati (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia's economic progress. In addition to providing a significant number of jobs, MSMEs also have the potential to create various business opportunities that support regional economic growth and contribute greatly to the distribution of development outcomes. This study aims to analyze the Strategy for Increasing the Competitiveness of Pecel Sambal MSMEs in Madiun City. The data analysis methods used in this study include descriptive analysis, IFE and EFE matrix analysis, IE matrix analysis, SOAR analysis, and QSPM matrix analysis. The results of the study indicate that the identification of internal factors (total IFE score) with a value of 3.27 is classified as strong, with the highest internal factor coming from “Durable products suitable for souvenirs” with a score of 0.5091. The factor of durable products suitable for souvenirs, which is a strength of sambal pecel processing SMEs, indicates that the products have durable characteristics, making them suitable as souvenirs. The EFE matrix analysis of 3.26 is classified as high, with external factors originating from “Government program support for MSMEs” with a score of 0.5059. Government program support aims to advance MSMEs, increase competitiveness, and encourage economic growth in the Madiun City area.